MOOC as an Alternative for Teaching and Learning During Covid-19 Pandemic: Students’ Motivation and Demotivation - Reza Anggriyashati Adara (Celt: A Journal of Culture, English Language Teaching & Literature, 2021)
Covid-19 pandemic has forced educators and students to use online learning instead of real-life classrooms. One of the learning platforms that seems to be popularly used during the pandemic is MOOC (Massive Open Online Course). The present study aims to analyze the motivation dan demotivation factors of Indonesian EFL learners toward MOOC by using a qualitative descriptive method. In order to obtain the results, ten respondents were interviewed. The interview results were transcribed and analyzed using NVivo software. Based on the present research’s findings, despite relatively positive attitudes toward MOOCs shown by the majority of respondents, the respondents were demotivated by MOOCs because they can get easily distracted when learning through MOOCs, they get lack feedback from tutors and peers and unreliable internet connections. However, the respondents are motivated to join MOOCs because MOOCs provide diverse subjects, encourage students to be autonomous, and provide effective and flexible learning. The results suggest that MOOCs can be an effective alternative for EFL teaching and learning during the pandemic but MOOCs need to be provided with better interaction between students and tutors to reduce students’ demotivation and encourage more positive attitudes as well as motivation.